Management information systems: managing the digital firm - Laudon, Kenneth C. (New Lersey: Prentice Hall, 2002)
Sus temas principales son: Organizations, management, and the networked enterprise. Information technology infrastructure. Building information systems in the digital firm. Managing information systems in the digital firm
Incluye bibliografía
Keywords: Management Information - Systems